Heating and Cooling Rate Study on Water Cooling Thermal Cycler using Aluminium Block Sample - Nugroho Budi Wicaksono; Sukma Meganova Effendi (Department of Electromedical Engineering, POLTEKKES KEMENKES SURABAYA and IKATEMI, 2022)
Temperature measurement has many applications in medical devices. In recent days, body temperature become the main screening procedure to justify people infected by SARS-CoV-2. Related to pandemic situation due to SARS-Cov-2, Polymerase Chain Reaction (PCR) method become the most accurate and reliable detection method. This method employs a device named PCR machine or Thermal Cycler. In this research, we focus to build a Thermal Cycler using a low-cost material such as aluminium and using a liquid coolant as the cooling system. We use 2 types of coolant solution: mineral water and generic liquid coolant. Peltier device in thermal cycler serves as heating and cooling element. In heating rate experiments, generic liquid coolant shows a better result than using mineral water due to specific heat capacity and thermal conductivity of water. In the cooling rate experiments, the water pump is activated to stream the liquid solution, the flow rate of liquid solution is influenced by viscosity of the liquid. Generic liquid coolant has approx. 4,5 times greater viscosity than water. The higher flow rate means better performance for cooling rate. Using 2 pieces of 60-Watt heaters and a 60-Watt chiller and aluminium material as block sample, our research shows a heating and cooling rate up to approx. 0,1°C/s. Compared to commercially thermal cycler, our thermal cycler has a lower wattage; this lower wattage performance has been tradeoff with lower ramping rate. Some factors are suspected become the source of contributors of lower ramping rate.